2009
DOI: 10.1111/j.1443-1661.2009.00838.x
|View full text |Cite
|
Sign up to set email alerts
|

Urgent Capsule Endoscopy Is Useful in Severe Obscure‐overt Gastrointestinal Bleeding

Abstract: Aim: With capsule endoscopy (CE) it is possible to examine the entire small bowel. The present study assessed the diagnostic yield of CE in severe obscure-overt gastrointestinal bleeding (OOGIB). Methods: During a 3-year period, 15 capsule examinations (4.5% of all CE in a single institution) were carried out in 15 patients (11 men; mean age 69.9 Ϯ 20.1 years) with severe ongoing bleeding, defined as persistent melena and/or hematochezia, with hemodynamic instability and the need for significant red blood cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 29 publications
0
39
0
3
Order By: Relevance
“…The timing of capsule endoscopy is paramount for success in finding a source of bleeding [13]. Previous investigators demonstrated a 73.3% yield for VCE in their evaluation of obscure-overt gastrointestinal bleeding, with an average time from admission to VCE of 4.1 days.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of capsule endoscopy is paramount for success in finding a source of bleeding [13]. Previous investigators demonstrated a 73.3% yield for VCE in their evaluation of obscure-overt gastrointestinal bleeding, with an average time from admission to VCE of 4.1 days.…”
Section: Discussionmentioning
confidence: 99%
“…It is responsible for 2–10% of the cases of digestive bleeding [2]. It is considered severe (1% of all cases) if any of the following is present: overt presentation, recurrent episodes of acute bleeding, transfusion dependence, and need for hospitalization [3].…”
Section: Discussionmentioning
confidence: 99%
“…CE allows the examination of the entire small bowel with similar diagnostic yield, and double-balloon enteroscopy permits real-time exploration with the advantage of therapeutic approach [2]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obscure gastrointestinal bleeding (OGIB) is blood loss from an unknown source that persists or recurs after negative investigations including esophagogastroduodenoscopy (EGD), colonoscopy and radiologic evaluation [1]. OGIB is the initial classification in about 5% of all patients with bleeding from the digestive tract [2]. OGIB originates most commonly from the small intestine; the jejunoileum is reportedly subsequently identified as the origin of bleeding in 75% of patients initially classified as having OGIB [1,3-5].…”
Section: Introductionmentioning
confidence: 99%